Oxygen governs gonococcal microcolony stability by enhancing the interaction force between type IV pili. Issue 10 (20th April 2015) - Dewenter, Lena; Volkmann, Thorsten E.; Maier, Berenike
Abstract : Bacterial cell clusters disassemble after having depleted oxygen because the interaction force between their surface appendages is reduced. Abstract : The formation of small bacterial clusters, called microcolonies, is the first step towards the formation of bacterial biofilms. The human pathogen Neisseria gonorrhoeae requires type IV pili (T4P) for microcolony formation and for surface motility. Here, we investigated the effect of oxygen on the dynamics of microcolony formation. We found that an oxygen concentration exceeding 3 μM is required for formation and maintenance of microcolonies. Depletion of proton motive force triggers microcolony disassembly. Disassembly of microcolonies is actively driven by T4P retraction. Using laser tweezers we showed that under aerobic conditions T4P–T4P interaction forces exceed 50 pN. Under anaerobic conditions T4P–T4P interaction is severely inhibited. We conclude that oxygen is required for gonococcal microcolony formation by enhancing pilus–pilus interaction.